Effect of carboxylic anhydride treatments on physical and mechanical properties of Hevea brasiliensis Mull.Arg., Acacia mangium Willd. and Elaeis guineensis Jacq. wood - Mohtar, Mohd Afiq (2015)
The objectives of the study was to investigate the reactivity of acid anhydride treatments, to determine the physical and mechanical properties and anti-swelling efficiency(ASE) as well as its relation between the properties. The rubberwood (Hevea brasiliensis), acacia (Acacia mangium) and oil-palm wood (Elaeis guineensis.) were modified with acetic, propionic and butyric anhydride in this study. The sample were cut into size of 300 mm X 100 mm X 25 mm (L X W X T) and vacuum impregnated before being reacted using a microwave. The scanning electron microscopy(SEM) observations shows that no damage occur to the cell wall structures during the modification procedure takes place while the fourier transform infrared (FTIR) analysis indicates that the bonding of cell wall polymer hydroxyl group with anhydride did happened. The results showed that the Oil palm wood(OPW) retained the highest anhydride solution followed by rubberwood and acacia with regardless of anhydrides. In contrast to uptake, the weight percent gain(WPG) was highest in rubberwood followed by OPW and acacia, regardless of anhydride. Overall, the modified rubberwood had a higher bulking coefficient (BC) followed by acacia and OPW. The result of density increment shows that the wood density was increased due to the modification process for all species. The void volume changes were negative for all wood species, except for acacia modified with acetic and butyric anhydride. Generally, treatment of wood with anhydride did not give any improvements to modulus of rupture(MOR) and modulus of elasticity(MOE). The compression strength was improved in modified rubberwood and acacia, but not in modified OPW. The hardness was not improved with either treatment with anhydride and this trend was consistent with all wood species. Regardless of anhydride, the impact strength was improved in modified rubberwood and OPW, but not in the case of acacia. Generally, modified rubberwood and acacia with propionic anhydride gave the highest ASE (4th cycle). Overall, the maximum improvement in terms of dimensional stability and mechanical properties was achieved in modified rubberwood and acacia with butyric anhydride.